DYNAMIC ANALYSIS OF A FLUIDIZED-BED REACTOR FOR SUCROSE INVERSION CATALYZED BY IMMOBILIZED INVERTASE - DOGU, T; KALETUNC, G; CAGLAR, A (Canadian Soc Chemical Engineering, 1985)
[Abstract Not Available]